Seeds of the future in the Present: Exploring the Intersections of [placemaking] through the Anatomic-Tectonic and Nature Reconnection Practices - Bester, Saajidah (School of Architecture, Planning and Geomatics, 2024)
This dissertation emerges from a deep-seated personal attachment to the Bo-Kaap, not only as a site of historical and cultural significance, but as a dynamic learning landscape that instilled within me a profound appreciation, connection, and love for the natural environment. Focused on the St Monica's precinct of Bo-Kaap, this research explores the concept of placemaking, uncovering the critical role of nature in fostering a sense of self through embodied pedagogical practices. The research emphasizes the significance of place memory and identifies the mountain as a powerful mnemonic, central to the understanding of the locality. The design aims to address these aspects through both architectural and landscape interventions, transforming vacant spaces within a dormant vicinity into thriving communal areas. This is translated into a design that seeks to be a gateway to nature, a vibrant learning landscape, and a hub for support facilities. The design intervention recognizes the need to restructure the social order of the Bo-Kaap, a historically rich neighbourhood currently facing socio-cultural challenges. By prioritizing the essence of place, (nature) and by developing the St Monica's Precinct as a [special place] and link to the mountain, to reconnect individuals with their environment and to foster a renewed sense of belonging and cultural identity